Long‐term variability of blood pressure and incidence of heart failure among individuals with Type 2 diabetes - Kaze, Arnaud D. (ESC Heart Fail, 2021)
AIMS: Data on the association of long‐term variability of blood pressure (BP) with incident heart failure (HF) in individuals with Type 2 diabetes are scarce. We evaluated this association in a large community‐based sample of adults with Type 2 diabetes. METHODS AND RESULTS: A total of 4200 participants with Type 2 diabetes who had available BP measurements at four visits (baseline and 12, 24, and 36 months) in the Look AHEAD (Action for Health in Diabetes) study were included. Variability of systolic BP (SBP) and diastolic BP (DBP) across the four visits was assessed using four metrics. Participants free of HF during the first 36 months were followed for HF events. Cox regression was used to generate hazard ratios (HRs) and 95% confidence intervals (CIs) for HF. Of the 4200 participants, the average age was 59 years [standard deviation (SD): 6.8]; 58.5% were women. Over a median follow‐up of 6.7 years, 129 developed HF events. After adjusting for relevant confounders, the HR of incident HF for the highest vs. lowest quartile of SD of SBP was 1.77 (95% CI 1.01–3.09); the HR for the highest (vs. lowest) quartile of variability independent of the mean of SBP was 1.29 (95% CI 0.78–2.14). The adjusted HR for participants in the highest (compared with the lowest) quartile of SD of DBP was 1.61 (95% CI 1.01–2.59), and the adjusted HR for variability independent of the mean of DBP was 1.65 (95% CI 1.03–2.65). CONCLUSIONS: A greater variability in SBP and DBP is independently associated with greater risk of incident HF in individuals with Type 2 diabetes.